Dynamical evolution of a minor sudden stratospheric warming in the Southern Hemisphere in 2019 - Liu, Guangyu; Hirooka, Toshihiko; Eguchi, Nawo; Krüger, Kirstin (Atmospheric Chemistry and Physics, 2022)
A major strong sudden stratospheric warming (SSW) occurred in the Southern Hemisphere (SH) stratosphere in 2002 (hereafter referred to as SSW2002), which is one of the most unusual winters in the SH. Following several warmings, the polar vortex broke down in midwinter. Eastward-traveling waves and their interaction with quasi-stationary planetary waves played an important role during this event. This study analyzed the Japanese 55-year reanalysis (JRA-55) dataset to examine the SSW event that occurred in the SH in 2019 (hereafter referred to as SSW2019). In 2019, a rapid temperature increase and decelerated westerly winds were observed at the polar cap, but since there was no reversal of westerly winds to easterly winds at 60∘ S in the middle to lower stratosphere, the SSW2019 was classified as a minor warming event. The results showed that quasi-stationary planetary waves of zonal wavenumber 1 developed during the SSW2019. The strong vertical component of the Eliassen–Palm flux with zonal wavenumber 1 is indicative of pronounced propagation of planetary waves to the stratosphere. The wave driving in September 2019 was larger than that of the major SSW event in 2002. Major SSWs tend to accompany preceding minor warmings, preconditioning, which changes the zonal flow that weaken the polar night jet as seen in SSW2002. A similar preconditioning was hardly observed in SSW2019. The strong wave driving in SSW2019 occurred in high latitudes. Waveguides (i.e., positive values of the refractive index squared) were found at high latitudes in the upper stratosphere during the warming period, which provided favorable conditions for quasi-stationary planetary waves to propagate upward and poleward.